2016
DOI: 10.1186/s13054-016-1362-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CX3CR1 messenger RNA expression is an independent molecular biomarker of early and late mortality in critically ill patients

Abstract: BackgroundChemokine (C-X3-C motif) receptor 1 (CX3CR1) was identified as the most differentially expressed gene between survivors and non-survivors in two independent cohorts of septic shock patients and was proposed as a marker of sepsis-induced immunosuppression. Whether such a biomarker is associated with mortality in the heterogeneous group of critically ill patients is unknown. The primary objective of this study was to evaluate the association between CX3CR1 messenger RNA (mRNA) expression and mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…Relative standard curves describing the PCR efficiency of selected targets were created and used to perform efficiency-corrected quantification with the LightCycler Relative Quantification Software. Targets expression normalization was performed using a selected housekeeping gene (hypoxanthine phosphoribosyltransferase 1 [HPRT1, (Friggeri et al 2016)]), and results were expressed as normalized concentration ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Relative standard curves describing the PCR efficiency of selected targets were created and used to perform efficiency-corrected quantification with the LightCycler Relative Quantification Software. Targets expression normalization was performed using a selected housekeeping gene (hypoxanthine phosphoribosyltransferase 1 [HPRT1, (Friggeri et al 2016)]), and results were expressed as normalized concentration ratio.…”
Section: Methodsmentioning
confidence: 99%
“…We found that 193 probesets, which represented 168 distinct HERV/MaLR loci, were differentially expressed in septic shock patients, depending on their immunosuppression status at day 3. The potential for stratification using these HERV/MaLR loci was validated on an independent cohort, with the identification of a severely affected group that had higher SOFA scores, decreased CX3CR1 expression (molecular marker associated with survival) [38], decreased CD74 and mHLA-DR expression (associated with HAI) [28,55], and increased S100A9 expression (associated with increased risk of secondary infections and mortality) [56]. As this pilot study was designed as a proof of concept study to show that HERV transcriptome can reflect the immune status, larger studies that involve higher numbers of patients are now warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, when we examined the expression of molecular markers, all were significantly different between the two clusters. The markers were HLA-DRA [36], S100A9 [37], CX3CR1 [38] expression on day 3, and CD74 ratio (D3/D1) [28], which are all linked to the immune system and were previously shown to be prognostic biomarkers (with either mortality or secondary infections) ( Table 2 and extended Additional file 8: Table S3). Severity criteria, outcomes, and molecular markers confirmed that cluster 1 contains more severely affected patients.…”
Section: Herv/malr Loci Can Differentiate Septic Shock Patients Accormentioning
confidence: 99%
“…Apart from surgical control of bleeding, management of major hemorrhage may include massive transfusions to maintain adequate circulation and hemostasis [6][7][8][9][10][11]. The transfusions include packed red blood cells (RBCs), plasma, and platelets (PLTs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The most important parameters to monitor in intensive care units are WBC, RBC and PLTs [21]. Current European guidelines on the management of hemorrhage following trauma [6] recommend early and repeated monitoring of PLT count to predict the proper PLT transfusion regimen. In patients with ongoing bleeding frequent bedside measurement of PLT count could aid the clinician in transfusing or withholding PLTs.…”
Section: Introductionmentioning
confidence: 99%